VARIABILITAS KONSENTRASI KLOROFIL-a DI PERAIRAN KALIMANTAN BARAT MENGGUNAKAN DATA MODIS AQUA - Dewi Merdekawati; Nurul Fatimah Yunita; Muhammad Usman (JURNAL MINA SAINS, 2021)
Chlorophyll-a is one of the important parameters in determining the amount of primary productivity in a waters. The purpose of this study was to examine the variability of chlorophyll-a in the waters of West Kalimantan. The data used is monthly and annual level 3 data for 5 years from 2016 – 2020 taken from the Aqua MODIS (Moderate-Resolution Imaging Spectroradiometer) satellite. The distribution of chlorophyll-a in the waters of West Kalimantan shows that the highest concentration value is found in coastal areas and the lowest in offshore waters. Meanwhile, the monthly distribution of chlorophyll-a showed that the highest concentration of chlorophyll-a was in August at 28.93 mg/m3 and the lowest was in December at 19.42 mg/m3.